Accurate Registration between Ultra-Wide-Field and Narrow Angle Retina Images with 3D Eyeball Shape Optimization - Zhang, Junkang; Wen, Bo; Kalaw, Fritz Gerald P.; Cavichini, Melina; Bartsch, Dirk-Uwe G.; Freeman, William R.; Nguyen, Truong Q.; An, Cheolhong (2023 IEEE International Conference on Image Processing (ICIP), 2023)
The Ultra-Wide-Field (UWF) retina images have attracted wide attentions in recent years in the study of retina. However, accurate registration between the UWF images and the other types of retina images could be challenging due to the distortion in the peripheral areas of an UWF image, which a 2D warping procedure can not handle. In this paper, we propose a novel 3D distortion correction method which sets up a 3D projection model and optimizes a dense 3D retina mesh to correct the distortion in the UWF image. The corrected UWF image can then be accurately aligned to the target image using 2D alignment methods. The experimental results show that our proposed method outperforms the state-of-the-art method by 30%.